An Unusual Case of Lyme Carditis With Persistent Third-Degree Heart Block - Niyati Grewal MD; John Gharbin MD; Prafulla Mehrotra FACC (SAGE Publishing, 2023)
Lyme's carditis and neuroborreliosis are common manifestation of disseminated Lyme disease. However, third-degree atrioventricular blocks with Lyme's carditis requiring permanent pacemaker with neuroborreliosis and Lyme's disease-associated immunodeficiency are uncommon. Here we present a case of 64-year-old female presenting with neurological symptoms and electrocardiogram changes suggestive of complete heart block with no improvement in the degree of heart block with intravenous antibiotics, requiring permanent pacemaker implantation and course complicated by fungemia.